2017
DOI: 10.1158/2326-6066.cir-16-0390
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Cells Express More Androgen Receptor (AR) Following Androgen Deprivation, Improving Recognition by AR-Specific T Cells

Abstract: Androgen deprivation is the primary therapy for recurrent prostate cancer, and agents targeting the androgen receptor (AR) pathway continue to be developed. Because androgen-deprivation therapy (ADT) has immmunostimulatory effects as well as direct antitumor effects, AR-targeted therapies have been combined with other anti-cancer therapies, including immunotherapies. Here, we sought to study whether an antigen-specific mechanism of resistance to ADT (overexpression of the AR) may result in enhanced AR-specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Considering that androgens and ARs are valuable targets of PCa treatment, and that their therapeutic benefit is somewhat limited by autophagy, our preliminary studies suggest that autophagy modulation might further improve malignant biological behavior, such as apoptosis and tumor growth, but have no influence on invasion and metastasis (Culig and Santer 2014;Olson et al 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Considering that androgens and ARs are valuable targets of PCa treatment, and that their therapeutic benefit is somewhat limited by autophagy, our preliminary studies suggest that autophagy modulation might further improve malignant biological behavior, such as apoptosis and tumor growth, but have no influence on invasion and metastasis (Culig and Santer 2014;Olson et al 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, WWTR1 and YAP1_PS127 both belong to the Hippo signaling pathway, and they are frequently hyperactivated in cancer (57). For the proteins that increased with ERRα/ABCC4 alteration, AR (androgen receptor) is expressed in primary and metastatic PCa, and downregulation of AR is considered a potential therapy for PCa (58,59). CHEK2 is a gene involved in DNA repair and its mutation is associated with PCa (60).…”
Section: Discussionmentioning
confidence: 99%
“…From a slightly different perspective, a study by Olson et al showed that prostate cancer cells express higher levels of AR upon androgen deprivation, which in turn improves recognition of tumor cells by AR-specific T cells ( 144 , 145 ). Therefore, direct targeting of the AR could be a promising immunotherapeutic approach.…”
Section: The Role Of Androgens In Anti-cancer Immune Therapymentioning
confidence: 99%